Imperialist Planning and Educational-Cultural Policy of the Axis Powers in Greece during World War II - Chatzistefanidou, Sofia (Preschool and Primary Education, 2020)
This paper examines the policies applied in Greece during World War II by the Axis occupational powers - Germany, Italy, and Bulgaria - in the fields of education and culture. Methodologically it is attempted that the policies concerned are interpreted and better highlightened through the presentation (a) of the profile of each of the countries involved and their mutual relations with Greece, as they were formed during the time of the development of nation states and their respective nationalisms, and (b) of the nationalistic incentives and geopolitical aspirations tracked behind the imperialistic designs of each occupying power. The ultimate goals of the occupiers can be summarized as follows: Dehellenization or expelling of Greek populations in Greek territories intended for future annexation to their nation states, degradation of the Greek language and culture, fascistization of the political system, and economic exploitation of the country.